Arte, fenomenología y cuerpo femenino - Cely Á., Flor Emilce (CALLE14: revista de investigación en el campo del arte, 2021)
This article presents two ways in which art and phenomenology are related. On the one hand, the family resemblance between phenomenology and the achievements of modern visual art in relation to a new way of understanding our visual encounter with the world and the gains at an experiential level that derive from it. And, secondly, the lessons that we can extract from the great creative and revolutionary artists to connect with our own experience, to find ourselves again with the new ways of seeing that they bequeathed us. In this sense, we will explore the art/phenomenology relationship with respect to the body, making a contrast with the scientific perspective on the subject, as well as an conducting an analysis of the artistic and scientific view of the body of women at the end of the 19th century and the beginning of the XXth.